ANALISIS BREAK EVEN POINT (BEP) DALAM PENETAPAN TARIF JASA TRANSPORTASI PADA PERUSAHAAN DAERAH JASA TRANSPORTASI KOTA BOGOR - Nurhayati, Immas; Rivai, Novan Mushaf (inovator, 2017)
The main purpose of this research is to analyze the tariffs of transportation services using break even point (BEP) model at the Regional Company Transport Service (PDJT) Bogor. This research tries to find the problem and alternative solution of PDJT financial performance based on tariffs and number of passengers. As the results of previous studies on the PDJT financial performance, that during the first trimester for January to March 2014, financial performance of PDJT was not good, the company couldn’t produce profits and suffered losses, this research also concluded thatinability to maintain the continuity of the company, other than caused by inefficiency, as demonstrated by the increasing fixed and variable costs per unit, also due to the transportationtariffs and number of passangers were too low. Something that can be the real solution to ensure the continuity of the company is efficiency, maintain tariffs rates on Rp. 4500 and increase in thenumber of passangers.